Case record review of adverse events: a new approach. - Woloshynowych, M; Neale, G; Vincent, C (2003)
OBJECTIVES: To redesign the existing clinical review form (RF2) used in previous retrospective case record review studies in order to clarify the review process and provide a more powerful analysis of adverse events; and then to ask clinicians to pilot and evaluate the new modular review form (MRF2). The review form is divided into five sections, each with a defined purpose, providing a modular structure. DESIGN: Design and testing of the MRF2 on a sample of medical and nursing records, and evaluation of the reviewers' responses regarding the new review form. SETTING: Hospital based teams from eight countries. RESULTS: The modular review form was reported to be comprehensive, well structured, and clear. Most of the reviewers agreed with the positive statements regarding the review form. Overall, the modular structure was thought to be helpful. Several modifications have been made to the final version to take account of criticisms and suggestions. CONCLUSIONS: The full potential of case record review has yet to be explored. The benefits of this review form include a modular format which enables reviewers or project leaders to select the focus of their review based on resources and the purpose of the review, and to identify contributory factors which indicate areas for improvement and prevention. The training of reviewers is of vital importance for record review. Record review remains one of the primary methods for assessing the incidence of adverse events and the new format is suitable for both prospective and retrospective review.